Koniec seansu. - Jaworski, Kazimierz Andrzej, b. 1897 ([Lublin] Wydawn. Lubelskie, 1970)
Autobiography of the Polish author.
Translated title: The end of the seance.
Keywords: Jaworski, Kazimierz Andrzej, -- 1897-; Authors, Polish -- 20th century -- Biography; Poland -- History -- 1918-1945.